Ag-Cu-Ti-Zr-B active composite brazing filler metal and application thereof

By developing the AG-CU-Ti-ZR-B active composite material, the residual stress and reliability problems in the connection between ceramics and metal welding are solved, and the high-intensity and reliable connection of ceramics and metals are realized.

CN119328363AActive Publication Date: 2025-01-21SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411527146.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-21
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

There are challenges in brazing connections between ceramics and metals, including efficient reduction of residual stress and improving long-term reliability of brazed joints.

Method used

Develop an Ag-Cu-Ti-Zr-B active composite solder that contains Ti and Zr as active elements. B is used to react with Ti or Zr in situ to form a reinforcing phase. The silver-copper alloy improves welding strength and ductility. sex.

Benefits of technology

A good connection between alumina ceramics and alloy alloys has been realized, with lower melting points and excellent mechanical properties, reducing the effects of thermal stress on the substrate, and improving the intensity and stability of the joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328363A_ABST
    Figure CN119328363A_ABST
Patent Text Reader

Abstract

The invention discloses an Ag-Cu-Ti-Zr-B active composite brazing filler metal and a preparation method of the Ag-Cu-Ti-Zr-B active composite brazing filler metal. The active composite brazing filler metal is composed of, by mass, 5%-8% of Ti, 2%-5% of Zr, 0.1%-2% of B and the balance Ag-28Cu eutectic components. The Ag-Cu-Ti-Zr-B active composite brazing filler metal prepared through the method has the advantages that the wettability is improved, the interface bonding strength is enhanced, the joint structure is refined, the brazing temperature is reduced, the fluidity and permeability are improved, and the heat resistance and corrosion resistance are improved. Due to the characteristics, the brazing filler metal becomes excellent brazing filler metal in ceramic metal brazing, and is particularly suitable for connection of high-performance ceramic and metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of welding materials, and more specifically, to an Ag-Cu-Ti-Zr-B active composite solder and its application. Background Art

[0002] Ceramics have the advantages of high melting point, high hardness, high temperature resistance, wear resistance, pressure resistance, acid and alkali resistance, high thermal conductivity, good thermal stability, and high mechanical strength. They are widely used in integrated circuits, aerospace ships, energy-saving smart cars, agricultural machinery, and biomedicine. However, ceramics have high hardness, high brittleness, and are easy to break. They are difficult to process. It is difficult to form them in one go using traditional processing and forming processes. Most of them are segmented and simply processed, and then composited with them to meet their service requirements for complex components. Ceramics are difficult to process due to their inherent characteristics, so their promotion and use in engineering are limited. The good compression plasticity and easy processing and forming properties of metals have attracted attention. At the same time, metal / ceramics have also received more and more attention in electronic packaging and other aspects. Therefore, combining ceramics with metals has become a research hotspot.

[0003] At present, there are many methods for ceramic / metal connection, mainly including mechanical connection, adhesive connection, self-propagating high temperature synthesis connection, ultrasonic connection, brazing, diffusion connection, local liquid phase transition connection, etc. Among them, brazing has many advantages, such as simple operation, less restrictions on joint size and form, good process repeatability and high joint strength. Therefore, it is often the preferred method for achieving reliable ceramic / metal connection.

[0004] Ceramic-metal brazing is an important research direction in the field of material connection. Due to the significant differences in the physical and chemical properties of ceramics and metals (such as thermal expansion coefficient, wettability, chemical stability, etc.), it is challenging to achieve reliable connection between the two. At present, the current status of ceramic-metal brazing research is mainly concentrated in the following aspects:

[0005] (1) Development of new brazing materials. In order to improve the wettability and interfacial bonding strength between ceramics and metals, researchers widely use brazing materials containing active elements (such as titanium, zirconium, chromium, tantalum, etc.). These active elements can react with oxides, nitrides or carbides in ceramics to form a chemical bonding layer, thereby enhancing the connection between ceramics and metals. For example, Ag-Cu-Ti alloy is a commonly used active brazing material for ceramic-metal brazing. Ti, as an active element, can react with oxides in ceramics to form titanium oxide, improving wettability and interfacial bonding strength.

[0006] (2) Research on interface reaction and bonding mechanism. The key to ceramic metal brazing is the reaction product and its structure at the interface. Current research shows that the active elements in the brazing material (such as Ti, Zr) can react with ceramic materials (such as Al2O3, Si3N4, SiC, etc.) to form compound layers with chemical bonding properties, such as TiC, TiN, TiO2, etc. These compound layers can form a strong metallurgical bond at the interface, thereby enhancing the strength and stability of the joint.

[0007] (3) Residual stress and failure mechanism. Due to the large difference in thermal expansion coefficients between ceramics and metals, residual stress will be generated during the brazing process, which may cause cracking of the ceramic material or joint failure. To address this issue, the researchers used a combination of finite element simulation and experimental testing to analyze the residual stress distribution in ceramic-metal joints and explored methods to reduce residual stress by optimizing joint design, selecting appropriate brazing materials, and controlling the brazing process.

[0008] With the application of new ceramic materials (such as alumina, aluminum nitride, silicon carbide, silicon nitride, etc.) in the electronics, aerospace and nuclear industries, researchers are actively exploring methods for brazing these ceramic materials with metals. According to the chemical properties of different ceramics, the development of brazing filler metals and brazing processes suitable for various ceramic materials is a current research hotspot. There have been many advances in the research of ceramic / metal brazing, including the optimization of brazing filler metals, the in-depth understanding of the interface bonding mechanism, and the development of advanced brazing technology. However, there are still some challenges, such as efficiently reducing residual stress and improving the long-term reliability of brazed joints. Future research directions will focus on the development of new brazing filler metals, fine-tuning of interface reactions, and the realization of high-performance ceramic / metal joints through advanced brazing processes. Summary of the invention

[0009] In order to overcome the deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide an Ag-Cu-Ti-Zr-B active composite brazing filler metal. The active composite brazing filler metal has a lower melting temperature and excellent mechanical properties, can achieve good connection between alumina ceramics and Kovar alloys, and is suitable for current actual production usage. In addition, the brazing filler metal is also suitable for a variety of brazing processes, and is flexible to operate. Compared with the existing preparation process, the preparation process of the active composite brazing filler metal of the present invention is simple and easy to operate, and has wide adaptability.

[0010] The second object of the present invention is to provide an application of Ag-Cu-Ti-Zr-B active composite solder.

[0011] The primary purpose of the present invention is achieved through the following technical solutions:

[0012] An Ag-Cu-Ti-Zr-B active composite solder comprises the following components in percentage by mass: 5-8% Ti, 2-5% Zr, 0.1-2% B, and the balance is Ag-28Cu eutectic component.

[0013] In the composition of the inventive solder, Ti and Zr are active elements, and B can react with Ti or Zr in situ to form a reinforcing phase.

[0014] Preferably, the Ag-Cu-Ti-Zr-B active composite solder comprises the following components in percentage by mass: 6% Ti, 3% Zr, 1% B, and the remainder is Ag-28Cu eutectic component.

[0015] Preferably, the Ag-Cu-Ti-Zr-B active composite solder comprises the following components in percentage by mass: 5% Ti, 5% Zr, 1% B, and the balance is Ag-28Cu eutectic component.

[0016] Preferably, the Ag-Cu-Ti-Zr-B active composite solder comprises the following components in percentage by mass: 6% Ti, 2.5% Zr, 0.5% B, and the remainder is Ag-28Cu eutectic component.

[0017] Preferably, the Ag-Cu-Ti-Zr-B active composite solder comprises the following components in percentage by mass: 8% Ti, 1.5% Zr, 1.5% B, and the remainder is Ag-28Cu eutectic component.

[0018] Preferably, the method for preparing the Ag-Cu-Ti-Zr-B active composite solder comprises the following steps:

[0019] (1) Weighing raw material powders according to mass percentage: 5-8% pure Ti powder, 2-4% pure Zr powder, 0.1-2% pure B powder, and the remainder being Ag-28Cu eutectic composition;

[0020] (2) mixing the raw material powder weighed in step (1) by ball milling;

[0021] (3) taking out the powder uniformly mixed in step (2), placing it in a vacuum drying oven for drying, and sieving to obtain solder alloy powder;

[0022] (4) adding an organic binder in small amounts and multiple times to the solder alloy powder in step (3), stirring evenly, and sealing and storing under vacuum at 0° C. to obtain a paste solder, i.e., Ag-Cu-Ti-Zr-B active composite solder;

[0023] The mass percentage of the solder alloy powder and the organic binder is 90% to 95%: 5% to 10%.

[0024] Preferably, the particle size of the Ag-28Cu eutectic component in step (1) is 50 μm; the particle size of the pure Ti powder is 30 μm, and its purity is above 99.9%; the particle size of the pure Zr powder is 20 μm, and its purity is above 99.9%; the particle size of the pure B powder is 200 nm, and its purity is above 99.9%.

[0025] Preferably, the mass percentages of silver and copper in the Ag-28Cu eutectic composition in step (1) are 72%:28%.

[0026] Preferably, the operation of loading the raw material powders in step (2) into the powder mixing bottle is carried out in a vacuum glove box, and the powder mixing bottle is filled with argon gas to isolate the influence of air on the mechanical mixing process of the raw material powders during ball milling.

[0027] Preferably, the specific conditions of the ball mill mechanical mixing in step (2) are: rotation speed 300-400 rpm, ball-to-material ratio 5:1, stainless steel grinding balls with diameters of 10 mm and 5 mm, and mixing time of 12-24 h.

[0028] Preferably, in step (3), the drying temperature is 50-80° C., the drying time is 3-6 hours, and the powder is sieved using a 300-mesh sieve.

[0029] Preferably, in step (4), the organic binder comprises the following components in percentage by mass: 40% modified rosin, 10% polyvinyl alcohol, 5% acetic acid, 30% anhydrous ethanol, 10% epoxy resin, 2% sodium lauryl sulfate and 3% carboxymethyl cellulose.

[0030] Preferably, the stirring time in step (4) is 5 to 10 minutes.

[0031] The second object of the present invention is achieved by the following technical solutions:

[0032] The invention discloses an application of Ag-Cu-Ti-Zr-B active composite solder in the connection between high-performance ceramics and metals.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The Ag-Cu-Ti-Zr-B active composite brazing material prepared by the present invention is applied to the brazing connection of alumina ceramics and cemented carbide, and can form a high-strength and reliable connection. The brazing material has good wettability to most ceramics and alloys and has strong adaptability. At the same time, it has a low melting point and can reduce the influence of thermal stress on the substrate.

[0035] (2) The Ag-Cu-Ti-Zr-B active composite solder prepared by the present invention is based on silver, copper and titanium, and zirconium and boron are added to modify the solder. The silver-copper alloy mainly plays a role in improving welding strength and ductility. The addition of silver can reduce the melting point, improve fluidity, and promote wettability with the substrate, thereby improving welding quality. At the same time, the silver-copper alloy exhibits good oxidation resistance at high temperatures, which helps to maintain the stability of the alloy during the welding process.

[0036] (3) The titanium in the Ag-Cu-Ti-Zr-B active composite brazing filler metal prepared by the present invention, as an active element, can react with oxygen in alumina ceramics to form titanium oxide compounds to achieve reliable connection. The zirconium in the brazing filler metal, as a strengthening element, reacts with aluminum in alumina ceramics to form stable intermetallic compounds, thereby improving the strength and hardness of the joint. The boron in the brazing filler metal can react with titanium to form TiB whiskers, which play a role in refining the grains and are conducive to obtaining a uniform microstructure.

[0037] (4) The preparation method of the Ag-Cu-Ti-Zr-B active composite solder of the present invention is highly flexible and relatively simple for studying the mechanism of action of various alloy elements on the silver-based solder. The composition ratio of each element can be freely controlled to control the changes in the microstructure and crystal structure of the solder alloy. It is simple and easy to study the microstructure, brittle phase distribution and mechanical properties of the brazed joint.

[0038] (5) The wetting angle of the Ag-Cu-Ti-Zr-B active composite solder prepared by the present invention on the surface of alumina ceramics is 17.5-30.5°, and the wetting angle on the surface of Kovar alloy is 9.1-19.7°; the shear strength of the joints of alumina ceramics and Kovar alloys prepared by the solder is 112-134 MPa, which is nearly 34% higher than the shear strength of the commercial solder. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly explain the technical aspects of the embodiments of the present invention, the drawings required in the description of the embodiments will be briefly described below.

[0040] Figure 1 The DSC curve of the Ag-Cu-Ti-Zr-B active composite solder prepared in Example 1;

[0041] Figure 2 The wetting angle of the Ag-Cu-Ti-Zr-B active composite brazing material prepared in Example 1 on the surface of alumina ceramics;

[0042] Figure 3 This is the wetting angle of the Ag-Cu-Ti-Zr-B active composite solder prepared in Example 1 on the Kovar alloy surface. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0044] Example 1 The mass percentages of the components in the active composite solder powder described in this example are: Ag-Cu28 alloy powder 90%, titanium powder 6%, zirconium powder 3%, and boron powder 1%.

[0045] The preparation method of the Ag-Cu-Ti-Zr-B active composite solder comprises the following steps:

[0046] (1) Ag-Cu28 alloy powder, titanium powder, zirconium powder and boron powder were weighed in a vacuum glove box according to the above ratios, and the weighed powders were placed in a powder mixing tank containing grinding balls with diameters of 10 mm and 5 mm, with the mixing ratio of balls to materials being 5:1;

[0047] (2) The powder mixing tank containing the powder was filled with argon gas and placed on a V-type powder mixer for mechanical mixing at a speed of 300 rpm for 24 hours. The mixed powder was placed in a vacuum drying oven to remove moisture at a temperature of 80°C for 4 hours;

[0048] (3) Finally, the dried powder is mixed with the pre-prepared organic binder in a ratio of 9:1, wherein the organic binder contains the following components in percentage by mass: 40% modified rosin, 10% polyvinyl alcohol, 5% acetic acid, 30% anhydrous ethanol, 10% epoxy resin, 2% sodium dodecyl sulfate and 3% carboxymethyl cellulose. The mixing process is carried out in a vacuum glove box. The organic binder is taken in proportion and put into a test tube, and 10% of the solder powder is weighed and put into the test tube each time, and stirred for 5 minutes. Observe whether the viscosity of each point in the solder paste is consistent. Stop stirring after reaching the standard; pour the solder paste into a syringe, seal it in a vacuum sealed bag, and store it at 0°C.

[0049] The Ag-Cu-Ti-Zr-B active composite brazing material prepared in this embodiment has a melting point of 784.0°C, a wetting angle of 18.4° on the surface of alumina ceramics, a wetting angle of 35.2° on the surface of Kovar alloy, and an average shear strength of brazing alumina ceramics and Kovar alloy of 134 MPa.

[0050] Figure 1 The DSC curve of the Ag-Cu-Ti-Zr-B active composite solder prepared in Example 1; Figure 2 The wetting angle of the Ag-Cu-Ti-Zr-B active composite brazing material prepared in Example 1 on the surface of alumina ceramics; Figure 3 The wetting angle of the Ag-Cu-Ti-Zr-B active composite solder prepared in Example 1 on the Kovar alloy surface.

[0051] Example 2 The mass percentages of the components in the active composite solder powder described in this example are: Ag-Cu28 alloy powder 89%, titanium powder 5%, zirconium powder 5%, and boron powder 1%.

[0052] The preparation method of the Ag-Cu-Ti-Zr-B active composite solder is as follows:

[0053] (1) According to the above ratio, weigh Ag-Cu28 alloy powder, titanium powder, zirconium powder and boron powder in a vacuum glove box respectively, and put the weighed powder into a powder mixing tank containing grinding balls with diameters of 10 mm and 5 mm. The ball-to-material ratio is 5:1.

[0054] (2) The powder mixing tank containing the powder was filled with argon gas and placed on a V-type powder mixer for mechanical mixing at a speed of 350 rpm for 24 hours; the mixed powder was placed in a vacuum drying oven to remove moisture at a temperature of 80°C for 4 hours.

[0055] (3) Finally, the dried powder is mixed with the pre-prepared organic binder at a ratio of 95:5, wherein the organic binder contains the following components in percentage by mass: 40% modified rosin, 10% polyvinyl alcohol, 5% acetic acid, 30% anhydrous ethanol, 10% epoxy resin, 2% sodium dodecyl sulfate and 3% carboxymethyl cellulose. The mixing process is carried out in a vacuum glove box. The organic binder is taken in proportion and placed in a test tube, and 10% of the solder powder is weighed and placed in the test tube each time, and stirred for 5 minutes. Observe whether the viscosity of each point in the solder paste is consistent, and stop stirring after reaching the standard. Pour the solder paste into a syringe, seal it in a vacuum sealed bag, and store it at 0°C.

[0056] The Ag-Cu-Ti-Zr-B active composite brazing material described in this embodiment has a melting point of 785.4°C, a wetting angle of 28.2° on the surface of alumina ceramics, a wetting angle of 30.4° on the surface of Kovar alloy, and an average shear strength of brazing alumina ceramics and Kovar alloy of 114 MPa.

[0057] Example 3 The mass percentages of the components in the active composite solder described in this example are: Ag-Cu28 alloy powder 91%, titanium powder 6%, zirconium powder 2.5%, and boron powder 0.5%.

[0058] The preparation method of the Ag-Cu-Ti-Zr-B active composite solder comprises the following steps:

[0059] (1) Ag-Cu28 alloy powder, titanium powder, zirconium powder and boron powder were weighed in a vacuum glove box according to the above ratios, and the weighed powders were placed in a powder mixing tank containing grinding balls with diameters of 10 mm and 5 mm; the mixing ball-to-material ratio was 5:1;

[0060] (2) The powder mixing tank containing the powder was filled with argon gas and placed on a V-type powder mixer for mechanical mixing at a speed of 350 rpm for 20 hours; the mixed powder was placed in a vacuum drying oven to remove moisture at a temperature of 80°C for 4 hours;

[0061] (3) Finally, the dried powder is mixed with the pre-prepared organic binder in a ratio of 9:1, wherein the organic binder contains the following components in percentage by mass: 40% modified rosin, 10% polyvinyl alcohol, 5% acetic acid, 30% anhydrous ethanol, 10% epoxy resin, 2% sodium dodecyl sulfate and 3% carboxymethyl cellulose. The mixing process is carried out in a vacuum glove box. The organic binder is taken in proportion and put into a test tube, and 10% of the solder powder is weighed and put into the test tube each time, and stirred for 10 minutes. Observe whether the viscosity of each point in the solder paste is consistent. Stop stirring after reaching the standard; pour the solder paste into a syringe, seal it in a vacuum sealed bag, and store it at 0°C.

[0062] The Ag-Cu-Ti-Zr-B active composite brazing material described in this embodiment has a melting point of 782.1°C, a wetting angle of 17.5° on the surface of alumina ceramics, a wetting angle of 27.1° on the surface of Kovar alloy, and an average shear strength of brazing alumina ceramics and Kovar alloy of 121 MPa.

[0063] Example 4 The mass percentage of each component in the active composite solder powder described in this example is: Ag-Cu28 alloy powder 89%, titanium powder 8%, zirconium powder 1.5%, and boron powder 1.5%.

[0064] The preparation method of the Ag-Cu-Ti-Zr-B active composite solder comprises the following steps:

[0065] (1) Ag-Cu28 alloy powder, titanium powder, zirconium powder and boron powder were weighed in a vacuum glove box according to the above ratios, and the weighed powders were placed in a powder mixing tank containing grinding balls with diameters of 10 mm and 5 mm, with the mixing ratio of balls to materials being 5:1;

[0066] (2) The powder mixing tank containing the powder was filled with argon gas and placed on a V-type powder mixer for mechanical mixing at a speed of 300 rpm for 24 hours. The mixed powder was placed in a vacuum drying oven to remove moisture at a temperature of 80°C for 4 hours;

[0067] (3) Finally, the dried powder is mixed with the pre-prepared organic binder at a ratio of 95:5, wherein the organic binder contains the following components in mass percentage: 40% modified rosin, 10% polyvinyl alcohol, 5% acetic acid, 30% anhydrous ethanol, 10% epoxy resin, 2% sodium dodecyl sulfate and 3% carboxymethyl cellulose. The mixing process is carried out in a vacuum glove box. The organic binder is taken in proportion and placed in a test tube. 5% of the solder powder is weighed and placed in the test tube each time. Stir for 10 minutes to observe whether the viscosity of each point in the solder paste is consistent. Stop stirring when the viscosity reaches the standard. Pour the solder paste into a syringe, seal it in a vacuum sealed bag, and store it at 0°C.

[0068] The Ag-Cu-Ti-Zr-B active composite brazing material described in this embodiment has a melting point of 790.6°C, a wetting angle of 30.5° on the surface of alumina ceramics, a wetting angle of 33.7° on the surface of Kovar alloy, and an average shear strength of brazing alumina ceramics and Kovar alloy of 112 MPa.

[0069] By comparing Examples 1 to 4 with existing solders, it can be seen that the Ag-Cu-Ti-Zr-B active composite solder of the present invention has good wettability with the base material, a lower melting point and a narrower melting range, and can ensure high-strength connection between alumina ceramic and Kovar alloy. The low melting point can effectively reduce the generation of oxidation and brittle phases during welding, and has a smaller melting zone, which is more conducive to metallurgical reactions during welding.

[0070]

[0071] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An Ag-Cu-Ti-Zr-B active composite solder, characterized in that: The invention comprises the following components in percentage by weight: 5-8% Ti, 2-5% Zr, 0.1-2% B, and the balance is Ag-28Cu eutectic component.

2. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The preparation method of the Ag-Cu-Ti-Zr-B active composite solder comprises the following steps: (1) Weighing raw material powders according to mass percentage: 5-8% pure Ti powder, 2-5% pure Zr powder, 0.1-2% pure B powder, and the remainder being Ag-28Cu eutectic composition; (2) mixing the raw material powder weighed in step (1) by ball milling; (3) taking out the powder uniformly mixed in step (2), placing it in a vacuum drying oven for drying, and sieving to obtain solder alloy powder; (4) adding an organic binder in small amounts and multiple times to the solder alloy powder in step (3), stirring evenly, and sealing and storing under vacuum at 0° C. to obtain a paste solder, i.e., Ag-Cu-Ti-Zr-B active composite solder; The mass percentage of the solder alloy powder and the organic binder is 90% to 95%: 5% to 10%.

3. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The particle size of the Ag-28Cu eutectic component in step (1) is 50 μm; the particle size of the pure Ti powder is 30 μm, and its purity is above 99.9%; The particle size of pure Zr powder is 20 μm, and its purity is above 99.9%. The particle size of pure B powder is 200 nm, and its purity is above 99.9%.

4. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The mass percentages of silver and copper in the Ag-28Cu eutectic composition in step (1) are 72%:28%.

5. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The operation of loading the raw material powder in step (2) into the powder mixing bottle is carried out in a vacuum glove box, and the powder mixing bottle is filled with argon gas to isolate the influence of air on the mechanical mixing process of the raw material powder during ball milling.

6. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The specific conditions of the ball mill mechanical mixing in step (2) are: a rotation speed of 300 to 400 rpm, a ball-to-material ratio of 5:1, stainless steel grinding balls with diameters of 10 mm and 5 mm, and a mixing time of 12 to 24 h.

7. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The drying temperature in step (3) is 50-80° C., the drying time is 3-6 hours, and the powder is sieved using a 300-mesh sieve.

8. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: In step (4), the organic binder comprises the following components in percentage by mass: 40% modified rosin, 10% polyvinyl alcohol, 5% acetic acid, 30% anhydrous ethanol, 10% epoxy resin, 2% sodium dodecyl sulfate and 3% carboxymethyl cellulose.

9. The Ag-Cu-Ti-Zr-B active composite solder according to claim 1, characterized in that: The stirring time in step (4) is 5 to 10 minutes.

10. Use of the Ag-Cu-Ti-Zr-B active composite brazing material according to any one of claims 1 to 9 in connecting high-performance ceramics to metals.

Citation Information

Patent Citations

  • Solder for connecting ceramics with kovar alloys

    CN106312369A

  • Laser brazing in-situ reaction AgCuTiZr solder and preparation method thereof

    CN110576275A

  • Paste of brazing filler metal and joined body using the same

    JP1992149075A

  • Filler metal for welding of al-zn-mg-cu base alloy and heat treatment of welding material using the filler metal

    JP2000317676A

Cited By

  • High-corrosion-resistance and high-strength solder and preparation method thereof

    CN119566614A

  • A high-corrosion-resistance and high-strength solder and its preparation method

    CN119566614B

  • A low-silver active solder and a method for preparing the same

    CN122975215A